Sketch-based interface and modelling of stratigraphy and structure in three dimensions. Issue 4 (2021) - Jacquemyn, Carl; Pataki, Margaret E. H.; Hampson, Gary J.; Jackson, Matthew D.; Petrovskyy, Dmytro; Geiger, Sebastian; Marques, Clarissa C.; Silva, Julio D. Machado; Judice, Sicilia; Rahman, Fazilatur; Sousa, Mario Costa
No abstract available